The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4172/2167-0943.1000126
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity among Adolescents in Kano, Nigeria

Abstract: Background: Childhood and adolescent obesity is a global public health concern because of associated increased risk of cardiovascular diseases later in life. Although there are several studies on childhood obesity in Nigeria, few have assessed it in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Due to varying epidemiologic, geographic, and economic dynamics prevalent in the study settings, the minimum sample sizes were estimated separately for Gombe and Uyo. In Gombe, the sample size was computed based on a prevalence of overweight/obesity of 2.82% from a previous study in Kano, northern Nigeria which is geographically and economically similar to Gombe [24]. In estimating the 377 adolescents studied in Gombe, a power of 80%, degree of precision of 2% [25], a 95% confidence interval, and a 10% parental refusal rate or i ncomplete data was assumed.…”
Section: Samplingmentioning
confidence: 99%
“…Due to varying epidemiologic, geographic, and economic dynamics prevalent in the study settings, the minimum sample sizes were estimated separately for Gombe and Uyo. In Gombe, the sample size was computed based on a prevalence of overweight/obesity of 2.82% from a previous study in Kano, northern Nigeria which is geographically and economically similar to Gombe [24]. In estimating the 377 adolescents studied in Gombe, a power of 80%, degree of precision of 2% [25], a 95% confidence interval, and a 10% parental refusal rate or i ncomplete data was assumed.…”
Section: Samplingmentioning
confidence: 99%
“…The study found that about 10% of the female adolescents were overweight/obese. While some of the existing studies reported similar prevalence rate of obesity among Nigerian adolescents [19,20,[26][27][28][29][30][31], a systematic review in Nigeria put the range between 1 − 11.4% [17]. Comparison to the existing studies in Nigeria is challenging because of the varying methodologies, and reference values used to define overweight and obesity, which might be responsible for the very wide range of the reported prevalence rates of adolescent obesity in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria's Benue state, prevalence of overweight and obesity in adolescent and children was 9.7 % and 1.8% respectively with rates being higher in children than in adolescents [5]. In Kano state, [13] reported a prevalence of 19.8% for overweight and 0.84% for obesity, while [50] reported 8.9% and 3.3% for respectively. [51] reported 10.3% overweight and 1.7% obesity in North Central Nigeria.…”
Section: Overweight and Obesity Trends Among School Children In Africamentioning
confidence: 99%
“…In sub-Saharan Africa the prevalence of overweight and obesity is more than 10% in many countries [8]. A number of studies have reported high and growing prevalence of more than 20% in childhood obesity across African nations, such as South Africa [11], Ghana [12], Nigeria [13], and Lesotho [14].…”
Section: Introductionmentioning
confidence: 99%